PEMBERDAYAAN KELUARGA PADA IBU NIFAS UNTUK MENCEGAH TERJADINYA BENDUNGAN ASI - Diyan Maria Kristin; Hasri Yulianti; Nurlaila Al Tadom (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
Breast milk engorgement is a common problem among postpartum mothers due to inadequate breast care and limited family support. This problem can hinder breastfeeding success and increase the risk of mastitis. This community service aimed to empower families in performing postpartum breast care to prevent breast milk engorgement. The methods used included health education, demonstration of breast massage, and family-assisted practice. The activity was conducted in Penfui Timur, District Kupang Tengah, in August 2025, involving 26 postpartum mothers and family members. The results showed a 45% increase in knowledge based on pre-test and post-test scores and a 60% improvement in practical breast care skills. Family support for breastfeeding mothers also improved significantly. This program proves that family empowerment effectively prevents breast milk engorgement and promotes exclusive breastfeeding success.